Selection of Scaffolding Materials Using AHP: Case Study of Puspem Gianyar - Made Sudiarsa; I Made Anom Santiana; I Gede Sastra Wibawa (Jurnal Ilmiah Telsinas, 2026)
The selection of scaffolding materials is a multi-criteria decision problem because safety, technical performance, cost, time, and operational considerations may lead to different preferences. This study evaluates wood, steel, and aluminum scaffolding for reinforced-concrete works in Building A of the Gianyar Government Center (Puspem Gianyar). A mixed-method design was applied using field observation, structured interviews, project documents, and pairwise-comparison questionnaires completed by 30 construction practitioners and experts. Respondents were selected purposively, and individual judgments were aggregated using the geometric mean before being processed with the Analytical Hierarchy Process (AHP). The revised reciprocal criteria matrix produced occupational safety as the highest-priority criterion (35.86%), followed by technical performance (27.09%), time (17.22%), cost (11.30%), and operational convenience (8.53%). The criteria matrix had a consistency ratio of 2.90%, while the sub-criteria matrices had a consistency ratio of 0.79%, both below the 10% acceptance threshold. After synthesizing criterion, sub-criterion, and alternative priorities, aluminum achieved the highest normalized final priority (41.77%), narrowly exceeding steel (40.88%), while wood obtained 17.35%. Aluminum performed strongly in durability, reuse, maintenance, installation efficiency, dismantling, and transportation, whereas steel remained superior in material strength, rigidity, and structural safety. The narrow difference between aluminum and steel indicates that the final decision remains sensitive to project-specific safety and technical requirements. The model offers a transparent decision-support framework rather than a universal material prescription.